Posterior Reversible Encephalopathy Syndrome presenting in late postpartum eclampsia challenging differential diagnosis (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Posterior reversible encephalopathy syndrome (PRES) is a severe neurological condition that presents with seizure, headache, visual impairment, accelerated hypertension, altered consciousness, and other neurological symptoms along with abnormal characteristic neuroimaging. Most of the cases are reversible. We described a case of a 31-year-old female with PRES secondary to delayed maternal postpartum eclampsia. The diagnosis was established after magnetic resonance imaging.J Bangladesh Coll Phys Surg 2024; 42: 297-300